Kajian Teoretis Kepemimpinan Motivasional dalam Pendidikan Islam: Integrasi Nilai Islam dan Path Goal Theory : Penelitian - Yuli Dwi Bina Margarini; Ika Verina; Rinawati; Agus Suwanto; Siswadi (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to comprehensively examine the theory of motivational leadership and its relevance within the context of Islamic educational leadership. The discussion focuses on fundamental leadership concepts, modern and traditional leadership theories, motivation in leadership, and the application of Path Goal Theory in Islamic educational institutions. The method employed in this study is a literature review, drawing on scholarly books and national and international journal articles related to leadership, motivation, and Islamic educational management. Data were analyzed using a descriptive-analytical approach to obtain an in-depth understanding of the relationship between motivational leadership, Islamic values, and educational performance. The findings indicate that motivational leadership in Islamic education is not solely oriented toward academic achievement but also emphasizes character building as well as moral and spiritual development of learners. Educational leaders who are able to integrate Islamic values such as trustworthiness (amanah), justice, consultation (shura), and exemplary conduct are proven to enhance teachers’ and students’ motivation, foster a positive organizational culture, and improve performance and learning quality. Furthermore, the application of Path Goal Theory provides a strategic framework for Islamic educational leaders to adapt their leadership styles to the needs and characteristics of their followers. This study confirms that motivational leadership grounded in Islamic values is a relevant and strategic approach to improving the quality and effectiveness of Islamic educational institutions.